Value of Calcium and Phosphorous in chronic kidney disease patients under hemodialysis: A retrospective study - Singh, S; Upadhyay-Dhungel, K; Aryal, G (Journal of Pathology of Nepal, 2012)
Background: Derangements of mineral metabolism occur during early stages of chronic kidney disease (CKD). Mineral metabolism has emerged as important predictors of morbidity and mortality in dialysis patients. This study aims to evaluate the values of calcium and phosphorous in reference to practice guidelines issued by National Kidney Foundation Dialysis Outcomes Quality Initiative (K/DOQI) in patients undergoing hemodialysis in KIST Medical College Teaching Hospital. Materials and Methods: It was a retrospective study which included 101 patients who underwent hemodialysis in KIST Medical College Teaching Hospital over a period of three months (October 2010 to December 2010). The laboratory parameters of serum calcium, and phosphorus were evaluated and were compared with that of recommended values by K/DOQI guidelines. Results: The mean values for serum calcium, phosphorus, and calcium-phosphorus product were 8.79 ± 1.48 mg/dL, 5.30 ± 1.32 mg/dL and 46.62 ± 1.96 mg2/dL2 respectively. Forty (40%), 53 (53%) and 76 (76%) cases of CKD patients met K/DOQI target value for calcium, phosphorous and calciumphosphorous product respectively. Twenty one percent of the patients meet the three K/DOQI guidelines and 14% did not meet any of the recommended guidelines by K/DOQI. Conclusion: To achieve all the K/DOQI guidelines multi-disciplinary team approach is crucial. More extensive multicenter studies need to be carried out. It is necessary to develop our national guidelines in future. Journal of Pathology of Nepal (2012) Vol. 2, 293-296 DOI: http://dx.doi.org/10.3126/jpn.v2i4.6881